Na caçada da onça: curraleira e sussa enquanto performances culturais quilombolas - Rocha, Maria Madalena do Sacramento (2019)
This dissertation aims to reflect on the Cultural Performance Sussa and Curraleira in the remaining Quilombo communities Extrema and Levantado, located in Iaciara-GO city. In this perspective, we seek to understand the historical contextualization of the place, from Macaúbas-BA to Extreme, Iracema district, in the municipality of Posse-GO. We analyzed the religious festivities, specifically the Levantada do Mastro, the Quilombos religious conflict with the Catholic Church, in the context of territorial certification and the visits of Lapinhas de Menino Jesus. At the same time, we identified the ties of kinship linking communities since the 1930s, the receipt of the “quilombola” identity given by the government through the Palmares Cultural Foundation, the updating of the concept of “Quilombo” and the emergence of the Associations, as a result of the titling. More specifically, we seek to detect from the research the memories and reports that constitute and build the “place” of Sussa and Curraleira cultural performances before and after the certification of the mentioned communities. Thus, it is possible to understand the relationship between space and place, from the experiences of religious festivals in Extrema and Levantado.